Modeling the role of marine protected areas on the recovery of shallow rocky reef ecosystem after a catastrophic submarine volcanic eruption. (March 2020) - Mendoza, José Carlos; Clemente, Sabrina; Hernández, José Carlos
Abstract: Modeling is a useful approach to learn about the capacity of the systems to recover after disturbances. In October 2011, a submarine volcanic eruption in The Punta Restinga–Mar de Las Calmas Marine Protected Area (RMC-MPA) caused catastrophic mass mortality. We modeled the recovery dynamics of the fully protected (no-take zone), partially protected (buffer zone), and unprotected (fished zone) areas to evaluate their resilience and their potential to restore fishing resources. Recovery varied with species and levels of protection. Benthic macroalgae and parrotfish populations recovered the fastest. Piscivore fishes, macroinvertebrate feeders, and macroinvertebrate detritivores required more extended recovery periods. The levels of protection played a significant role in recovery, with the no-take zone showing more resilience than the buffer and fished zones. Our results suggest that no-take zones are crucial in the recovery process after catastrophic events. Regular monitoring of benthic communities provided the necessary data to model these communities and to point to the regulation of the artisanal fleet activity in restricted fishing areas as a mechanism to further enhance the recovery of fishing stocks. Highlights: First Ecopath with Ecosim model of an MPA subject to a submarine volcanic eruption. Higher trophic levels required more extended recovery periods. The no-take areas are crucial in the recovery process after a catastrophic event. The MPA design with several no-take areas assures an increase of resilience.